Development and validation of a semi-automatic landmark extraction method for mesh morphing. (August 2019) - Wu, Jun; Cai, Meiling; Li, Junyi; Cao, Libo; Xu, Liangliang; Li, Na; Hu, Jingwen
Highlights: A semi-automatic landmark extraction method is proposed. The application of the method can effectively reduce the time in the process of developing parametric finite element models. The method has strong adaptability and can be applied to the finite element modeling of different human bones. Abstract: Currently, landmark-based mesh morphing technology is widely used to rapidly obtain meshes with specific geometry, which is suitable to develop parametric human finite element (FE) models. However it takes too much time for landmark extraction to obtain high geometric accuracy. The purpose of this study is to develop and validate a semi-automatic landmark extraction method to reduce the time of manual selection of landmarks without sacrificing the accuracy of identifying landmarks in the process of mesh morphing. A few contour edge landmarks were extracted manually. Mathematical landmarks and pseudo-landmarks were extracted automatically by user-defined algorithm. The radial basis function (RBF) was used to morph the baseline FE model into the target geometry based on these landmarks. The cervical vertebra (C5), rib (R7) and femur were selected as the target geometries to verify the effectiveness of the method. The maximum mean geometric error of the three types of target geometries was less than 1 mm. The mesh quality of the morphed FE model was similar to that of the baseline FE model. Compared to the traditional manual method, 2/3 to 3/4 of the time for landmark extraction was saved by the semi-automatic method.